Differential Regulation of Membrane CD14 Expression and Endotoxin-Tolerance in Alveolar Macrophages - Lin, Shu-Min (2004)
CD14 is important in the clearance of bacterial pathogens from lungs. However, the mechanisms that regulate the expression of membrane CD14 (mCD14) on alveolar macrophages (AM) have not been studied in detail. This study examines the regulation of mCD14 on AM exposed to Escherichia coli in vivo and in vitro and explores the consequences of changes in mCD14 expression. The expression of mCD14 was decreased on AM exposed to E. coli in vivo and AM incubated with lipopolysaccharide (LPS) or E. coli in vitro. Polymyxin B abolished LPS effects but only partially blocked the effects of E. coli. Blockade of extracellular signal-regulated kinase pathways attenuated LPS and E. coli-induced decrease in mCD14 expression. Inhibition of proteases abrogated the LPS-induced decrease in mCD14 expression on AM and the release of sCD14 into the supernatants, but did not affect the response to E. coli. The production of TNF-α in response to a second challenge with Staphylococcus aureus or zymosan was decreased in AM following incubation with E. coli but not LPS. These studies show that distinct mechanisms regulate the expression of mCD14 and the induction of endotoxin-tolerance in AM and suggest that AM function is impaired at sites of bacterial infection.